Good neighbours matter: economic geography and the diffusion of human rights - Edwards, T. Huw; Kernohan, David; Landman, Todd; Nessa, Azizun (Taylor & Francis, 2018)
We investigate the geo-political and economic aspects of human rights (HR) performance using multi-country panel data. HR performance depends on relative levels of economic development and spatial proximity to ‘good’ and ‘bad’ neighbours. We test for basic effects of income, and apply spatial weighting models, to analyse the neighbours’ impact on HR levels, treating this impact as partly endogenous. We take into account size and distance, to compare each country’s HR performance with what would be predicted from a weighted average of its neighbours’ performance. There are (a) geographical clusters and (b) size and proximity effects for HR performance.